The Principal's Role in Improving Teacher Performance at Junior High School of SMP Negeri 18 Sigi - Mohamad Arif; Idrus; Hasan; Ika Nurjayanti (Kirana Publisher (KNPub), 2026)
This study aims to determine the role of the principal in improving teacher performance and describe teacher performance at SMP Negeri 18 Sigi. This study uses a qualitative approach with a descriptive type. Data collection techniques were carried out through interviews, observations, and documentation with the research subjects of the principal and teachers. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the principal has a very important role in improving teacher performance which is carried out through the role of educator, manager, administrator, supervisor, leader, motivator, and entrepreneur. As an educator, the principal provides academic coaching and supervision to teachers. As a manager and administrator, the principal systematically manages school programs and administration. As a supervisor, the principal supervises and evaluates teacher performance. As a leader and motivator, the principal provides an example. Teacher performance at SMP Negeri 18 Sigi has generally been running well. This is seen from the ability of teachers to develop collaborative lesson plans, implement the learning process based on the RPP, and conduct assessments that include aspects of knowledge, attitudes, and skills. Teachers are also able to build good relationships with students and implement remedial programs to improve student learning outcomes. The conclusion is that the role of the principal is very influential in improving teacher performance, and teacher performance at SMP Negeri 18 Sigi is already considered good even though it still needs improvement, especially in the aspects of motivation and continuous development.